Mindset as Characteristic Adaptations: Using Response Surface Analysis to Assess Mindset in the Personality System - Ratchford, Juliette L.; Williams, Emily G.; Bishara, Leanne; Houltberg, Benjamin J.; Schnitker, Sarah A. (Frontiers in Psychology, 2021)
This study aimed to assess the congruencies and discrepancies between mindset domains in relation to well-being. This study sought to demonstrate that mindset falls into the characteristic adaptation level of personality. Data (N = 618, Mage = 16.07, SDage = 0.99) from Wave 1 of a longitudinal study on primarily ethnic-minority adolescents were used in response surface analyses to examine objectives. The response surface analyses suggested no overall congruence effect between moral and ability mindsets. However, two-thirds of the participants demonstrated differing levels of mindsets, highlighting the domain specificity of mindsets. Results suggest that mindsets are contextual, domain-specific constructs, suiting the characteristic adaptation level of personality. Congruence for moral and ability mindset does not affect adolescent well-being.